Pendidikan Dan Lingkungan Sosial - Banatul Khoiriah; Irpan Siregar Irpan Siregar; Dwi Puspita Sari Dwi Puspita Sari; Irvandy Anugrah Nasution Irvandy Anugrah Nasution (Jurnal Zeniusi, 2024)
Education is a process closely related to transmitting knowledge, attitudes, beliefs, skills, and other aspects of behavior to the younger generation. In this context, education teaches and shapes human behavior patterns according to societal expectations. This study aims to analyze the role of education in shaping individual social behavior through interactions in the family, school, and community environments. The method used is qualitative research with a library research approach, where data is collected from relevant literature. This study found that in primitive societies, formal education does not exist, and every child learns from their social environment without a specific teacher who is responsible for their behavior. However, in more advanced societies, formal education in schools becomes an important social institution in socializing individuals to become expected members of society. Formal education in schools has a major role in shaping individual personalities, where almost all individual behavior is influenced by others. In addition, this study also highlights the importance of the educational environment, which includes the family, school, and community environments, in influencing child development both consciously and unconsciously.